The Role Of Family and School Environment In Actualizing Children's Talents - Nurul Faradyah; Ike Utia Ningsih (CV. Era Digital Nusantara, 2025)
Children’s giftedness represents a potential that requires supportive environments for optimal development. This study aims to analyze the roles of family and school contexts in the actualization of giftedness. A descriptive qualitative method was employed through a literature review of relevant theoretical and empirical sources. The findings reveal that the family environment contributes by providing emotional support, appropriate parenting styles, and early stimulation of children’s abilities. Meanwhile, the school environment facilitates giftedness through adaptive learning strategies and teachers’ understanding of gifted children’s characteristics. The synergy between family and school emerges as a crucial factor in enabling children to optimally realize their potential. In conclusion, strengthening collaboration between these two environments is essential to ensure the holistic development and actualization of giftedness.